Female Entrepreneurship for Sustainable Economy and Development—Challenges, Drivers, and Suggested Policies for Resource-Rich Countries - Muneera Al-Qahtani (19489312) (2022)
Female entrepreneurship plays a critical role in achieving economic diversification, sustainable economy, and sustainable development, not only in economic terms but also in social and environmental dimensions. Women are considered excellent and relentless custodians of their families, their surroundings, and society. However, in many countries, particularly in resource-rich and developing states, there are considerably limited opportunities and barriers for women to utilize their utmost capacities. Considering the historical development trajectory and learning from several past and benchmark examples, mainly from the entrepreneurship domain, we first developed a conceptual model to deliver a holistic strategy for policymaking and implementation by employing design and systems thinking approaches. Second, based on this conceptual model, we proposed an integrated policy framework for Qatar, as a resource-rich country in the quest of transforming into an innovation-driven, knowledge-based sustainable development to propel women’s entrepreneurship and increase their involvement in achieving economic diversification, and thus, sustainable development in a broader perspective. Third, we conducted a survey to validate the feasibility and effectiveness of the proposed policy framework. Results reveal that surveyed aspiring and actual female entrepreneurs maintain the relevance of the suggested policies related to the provision of further local training and mentorship programs and subsidies and funds from the government. Furthermore, while female participants agree that their entrepreneurial practices need to abide by local cultural traditions and trends, they believe there is a supplementary need to spread awareness of and garner support for their social and economic contribution to the society. Finally, findings show that several female participants, mainly Qatari nationals, are willing to become entrepreneurial investors to help fund other entrepreneurship startups to partner with other women and give back to society and contribute to the overall sustainability of their community. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su142013412